2009
DOI: 10.1021/om900402e
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroaryl-Substituted Boron Dipyrrinato Complexes

Abstract: A methodology for the incorporation of fluoroaryl groups into boron dipyrrinato complexes (modified BODIPY dyes) is reported. Two hexaalkylated dipyrrinato ligands with either H or CH 3 occupying the meso position were employed; when they were treated with fluoroaryl haloboranes in the presence of a weak base, the title compounds were prepared in good to excellent yields. The structures of seven derivatives were determined using X-ray crystallography, and their spectroscopic, photophysical, and redox propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…Alternatively, mono-and disubstituted BODIPYs can be prepared by reaction of dipyrrins with haloboranes. 22,23 Recently, the synthesis of 4-chloro-4-phenyl-1,3,5,7,8-pentamethyl-BODIPY was reported from the corresponding dipyrrin hydrochloride salt, by reaction with sodium hydride followed by dichlorophenylborane; this BODIPY was sensitive to moisture and was rapidly converted into the corresponding 4-hydroxy-4-phenyl-BODIPY, which afforded 4-phenyl-BODIPY upon reaction with potassium bifluoride. 24 This methodology was employed for the [ 18 F]-radiolabelling of BODIPY for its investigation in positron emission tomography (PET)/fluorescence dual imaging.…”
mentioning
confidence: 99%
“…Alternatively, mono-and disubstituted BODIPYs can be prepared by reaction of dipyrrins with haloboranes. 22,23 Recently, the synthesis of 4-chloro-4-phenyl-1,3,5,7,8-pentamethyl-BODIPY was reported from the corresponding dipyrrin hydrochloride salt, by reaction with sodium hydride followed by dichlorophenylborane; this BODIPY was sensitive to moisture and was rapidly converted into the corresponding 4-hydroxy-4-phenyl-BODIPY, which afforded 4-phenyl-BODIPY upon reaction with potassium bifluoride. 24 This methodology was employed for the [ 18 F]-radiolabelling of BODIPY for its investigation in positron emission tomography (PET)/fluorescence dual imaging.…”
mentioning
confidence: 99%
“…With this in mind, we chose to investigate monoarylated BODIPY derivatives, a class of compounds that have been recently reported by Ziessel [12][13][14] as well as by Piers [9,10]. By adaptation of the work of Cowley on the synthesis of on b-diketiminate boron species [15], we allowed 3,5,3 0 ,5 0 ,6-pentamethyldipyrrin hydrochloride (1) [16] to react with sodium hydride (NaH) in diethyl ether/hexanes (1:1; v:v).…”
Section: Resultsmentioning
confidence: 99%
“…As part of our contribution to the general area of fluoride ion coordination to boron compounds, we have recently reported that cationic BODIPY compounds [9,10] such as A + react with fluoride anions in CHCl 3 to afford the corresponding BODIPY difluoride species [11]. Presumably, this reaction is facilitated by the lability of the DMAP ligand as well as the overall positive charge of A + .…”
Section: Introductionmentioning
confidence: 99%
“…The reactions of BODIPYs with lithiated arylethynes were very fast with the 4-monosubstituted compounds being undetectable (Scheme 140). 361,363 For this reaction, it was necessary for the parent BODIPY 94 to be highly substituted to prevent attack on the pyrrole 364 or meso-carbons (Scheme 128), 70,318,365 leading to side products or decomposition. Structure determinations of 4,4-dialkynylBODIPYs (e.g., 498 derived from 94) showed a somewhat distorted tetrahedral geometry for the sterically congested boron atoms.…”
Section: Reaction With O-nucleophilesmentioning
confidence: 99%